Perfil clínico epidemiológico e parâmetros laboratoriais em pacientes acometidos pela covid-19 em uma unidade de terapia intensiva - Teixeira, Denise Gonçalves dos Santos (2023)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, which began in 2019, has resulted in social and economic upheavals in several countries, with high rates of hospitalizations and deaths. Initially considered an infection of the respiratory tract only, COVID-19 has proved to be a systemic disease, causing functional deficits in several organs and systems both in the acute and chronic phases of the disease. Changes in several parameters, biochemical and hematological markers can provide critical support for the adequate clinical management of patients with COVID-19. The present study aimed to evaluate the clinical-epidemiological profile, laboratory changes and clinical outcome in 103 patients, aged 18 years or older, affected by COVID-19 in an Intensive Care Unit in the city of Ji-Paraná/Rondônia, from March 2021 to July 2022. Data were collected regarding gender, age, comorbidities or associated pathologies, dosage of C-reactive protein (CRP), urea, creatinine, sodium and potassium, glutamic-pyruvic transaminase (GPT) and glutamic-oxalacetic transaminase (GOT), type of ventilatory support, time of use of ventilatory support, length of stay in the ICU. Of the 103 patients admitted to the ICU, 51(49.5%) were female and 52 (50.5%) were male, and most patients (about 56%) were 60 years or older. Hypertension, Diabetes mellitus and heart disease were the most frequent comorbidities. The mean ICU stay was 8.7 days and 61.2% of patients required invasive ventilatory support. Of the patients analyzed, 36 (35.0%) were discharged from the ICU, 48 (46.6%) were transferred to another unit and 19 (18.4%) died. Of the transfers, 43.8% occurred due to acute kidney injury requiring dialysis support. CRP values were high in all groups, with a mean of 40.8 mg/L in the discharged group, 52.0 mg/L in the transferred group and 54.5 mg/L in the death group, however, only the group discharged from the ICU showed a significant reduction in CRP values before clinical outcome. Urea and creatinine revealed mean values of 66.5 mg/dL and 1.1 mg/dL in the discharge group, 76.8 mg/dL and 1.6 mg/dL in the transferred group and 94.6 mg/dL and 2.0 mg/dL in the death group, being higher in patients who died. Sodium and potassium measurements showed no significant changes. Elevated liver markers were identified in all study groups, however, with higher mean values in patients who progressed to worse outcomes, with mean GPT 104.2 U/L and GOT 142.7 U/L in patients who progressed to death. In addition, liver parameters may remain elevated even after ICU discharge. Alterations in inflammatory, renal and hepatic markers were associated with more severe COVID-19 conditions and worse outcomes, with the need for dialysis and/or respiratory support. The results of the study may contribute to the elucidation of clinicalepidemiological information and the main biochemical changes that occur in COVID-19 in ICU patients.